EFFECT OF PLANTING DATES AND TOMATO CULTIVARS ON INTENSITY OF EARLY BLIGHT CAUSED BY ALTERNARIA SOLANI (Journal of Plant Disease Sciences, 2017)
The effect of different dates of planting and cultivars on early blight disease intensity and yield of tomato was determined. Tomato crop was planted on three different dates during 2011 (D : 20.07.2011; D : 05.08.2011 and D : Kharif, 1 2 3 20.08.2011) and 2011 (D : 20.11.2011, 05.11.2011 and 20.11.2011), using Rabi, 1 two cultivars Mahyco 5005 (Tolerant) and Pusa Ruby (Susceptible). During Kharif, 2011 maximum average disease intensity was recorded in the crop transplanted on D (05.08.2011) and minimum on D (20.07.2011) and D Mahyco 5005 and 2 1 3 recorded minimum average disease intensity of 32.02 (D ), 32.11 (D ) and 42.10 1 3 (D ) per cent; whereas Pusa Ruby recorded maximum average disease intensity of 2 36.58 (D ), 41.46 (D1) and 45.88 (D ) per cent. During 2011 minimum average 3 2 Rabi, disease intensity was recorded in crop transplanted on D (20.12.2011) and 3 maximum on D (20.11.2011) and D (05.12.2011). In both the tomato cultivars 1 2 disease intensity from its first appearance was increased steadily and it was comparatively maximum in Pusa Ruby than Mahyco 5005. However, the yield of tomato was significantly higher in the crop planted during , 2011, as minimum Rabi disease intensity was observed than that of 2011. Kharif,
Keywords: Alternaria solani, disease intensity, sowing dates, Tomato